Jerusalem, Israel/Palästina. Archäologie (be)trifft Schule – Ein deutsch-palästinensisches Geschichtsprojekt in Jerusalem als Bildungs- und Friedensarbeit - Soennecken, Katja; Serr, Marcel (e-Forschungsberichte des DAI, 2017)
Palestinian Schoolgirls of the Schmidt’s Girls School in Jerusalem discover the history of their city together with archaeologists and historians from the German Protestant Institute of Archaeology in Jerusalem.